Nontrivial Solution of Fractional Differential System Involving Riemann-Stieltjes Integral Condition - Ge-Feng Yang (Abstract and Applied Analysis)
We study the existence and uniqueness of nontrivial solutions for a class of fractional differential system involving the Riemann-Stieltjes integral condition, by using the Leray-Schauder nonlinear alternative and the Banach contraction mapping principle, some sufficient conditions of the existence and uniqueness of a nontrivial solution of a system are obtained.